Analysis of outcomes of robot-assisted laparoscopic pyeloplasty in children from a tertiary pediatric center in South India - Vidhya, Tamizhvanan; Rajiv, Padankatti; Sripathi, Venkat (Frontiers in Pediatrics, 2024)
Aim This study aims to analyze the outcomes of robot-assisted laparoscopic pyeloplasty (RALP) in children with pelvi-ureteric junction obstruction (PUJO) over a 10-year period at a tertiary care center in South India. Methods This study provides a detailed analysis of prospectively acquired data from 2013 to 2023 of all children who underwent RALP at our institution. Pre- and post-operative renal ultrasound and isotope renography were used to assess outcomes. Detailed information on patient demographics, procedural duration, post-operative pain relief, operation steps, and post-surgical follow-up protocols has been provided. The analysis included all patients who completed a 1-year follow-up. Result Between 2013 and 2023, 201 children underwent RALP. Of these, 185 children completed at least 1 year of follow-up and were included in the analysis. The mean age of the cohort was 4.9 years (1 month to 17 years), with males comprising the majority (77.3%). Twenty-five children (13.5%) were younger than 1 year of age. Left-sided PUJO was found to be more common. The mean console time was 76.5 min (40–180 min), and the average hospital stay was 2.8 days (2–5). After surgery, the mean reduction in antero-posterior diameter of the renal pelvis was more than 50% of its pre-operative value and statistically significant (3.3 ± 0.3 to 1.9 ± 0.9 cm). At the end of 1 year, the overall reduction in renal size was also significant (9.7 ± 2.3 cm pre-operative to 8.9 ± 1.8 cm post-operative). The pre-operative Society of Fetal Urology (SFU) grade of hydronephrosis was compared to the post-operative SFU grade, and the improvement (resolution/downgrading) was found to be statistically significant. The median split renal function in this series was 39% pre-operative and 43% post-operative, and the overall functional improvement after RALP was significant. A successful outcome was observed in 181 children (97.8%). Four children experienced persistent severe hydronephrosis and underwent redo stenting and/or redo pyeloplasty (2.1% failure rate). Post-operative complications, according to the Clavien–Dindo classification, were classified as type 1 in three children and type 3b in two children. There were no conversions to open surgery in the series. Conclusion RALP emerges as the minimally invasive procedure of choice for children with PUJO at our institution. It is safe, delivering consistently excellent results and minimal complications. Our outcomes are comparable to those of previously published series. We trust that our experience will serve as a roadmap for those centers (especially in South Asia) embarking on a pediatric robotic program.